A PRELIMINARY STUDY ON THE PRAWN FISHERY OF BIG TRAWLERS ALONG THE NORTHEAST COAST OF INDIA - Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
The number of big trawlers operating along the northeast coast increased from 55 in 1983-84 to 76 in 1985-86, increasing the prawn landings from 2353 t in 1983-84 to 3043 t in 1985-86. Catch per hour of trawling reached a peak in 1984-85 (20.1 kg) and then declined in 1985-86 (16.5 kg). The proportion of ’tigers’ (8%), ’whites’ (30%) and ’browns’ (62%) was more or less stable during the three-year period. There was a gradual increase in abundance of ’tigers’ from 11 m depth to 60 m depth and a gradual decrease thereafter. The ’whites’ were more abundant in 11-40 m depth. The abundance of ’browns’ gradually increased from 11 m to 100 m depth. There are good fishing grounds in Sandheads I arid off Paradeep and Chilka for tigers’, off Paradeep, Gopalpur and Kalingapatnam and in Sandheads II for ’whites’, off Anchorage, Sunderbans and Gopalpur for ’browns’. The potential yield of prawns from the trawling grounds between Pentakota and the Sunderbans is estimated at 6559 t. As the present harvest from this region is 5424 t, there is scope for an addition of 28 more trawlers to the existing fleet of 76.